Sesquiterpene lactone containing extracts from two cultivars of forage chicory (Cichorium intybus) show distinctive chemical profiles and in vitro activity against Ostertagia ostertagi - Miguel Peña-Espinoza; Ulrik Boas; Andrew R. Williams; Stig M. Thamsborg; Henrik T. Simonsen; Heidi L. Enemark (International Journal for Parasitology: Drugs and Drug Resistance, 2015)
The study investigated direct anthelmintic effects of sesquiterpene lactones (SL)-containing extracts from forage chicory against free-living and parasitic stages of Ostertagia ostertagi. Freeze-dried leaves from chicory cultivars ‘Spadona’ and ‘Puna II’ were extracted using methanol/water. Total SL were further fractionated by solid-phase extraction and resulting extracts were characterised by high-performance liquid chromatography (HPLC). O. ostertagi eggs from faeces of mono-infected calves were hatched and L1 were used in a larval feeding inhibition assay (LFIA), while cultured L3 were used in a larval exsheathment inhibition assay (LEIA). Adult worms were immediately recovered after slaughter and used for motility inhibition assays (AMIA). Electron microscopy (EM) was performed on adult O. ostertagi exposed to 1000 μg extract mL−1 of both chicory cultivars. In all assays, decreasing concentrations of SL-containing extracts in PBS (1% DMSO) were tested in replicates with 1% DMSO in PBS as negative controls. HPLC demonstrated similar concentrations of most SL in both extracts. However, Spadona-extract contained significantly higher concentrations of 11, 13-dihydro-8-deoxylactucin (P = 0.01), while Puna II-extract had increased levels of 11, 13-dihydrolactucin (P < 0.0001). In the LFIA, both extracts reduced larval feeding at increasing concentrations, but Spadona-extract showed higher potency confirmed by significantly lower EC50 (P < 0.0001). In the LEIA, neither of the two extracts interfered with the exsheathment of L3 (P > 0.05). In the AMIA, both SL-containing extracts induced a dose-dependent effect but Spadona-extract showed greater activity and exerted faster worm paralysis than Puna II-extract with significantly lower EC50 (P < 0.0001). No cuticular damage was observed by EM in worms exposed to any of the extracts. We have demonstrated that SL-containing extracts from forage chicory can inhibit feeding of free-living larvae and exert direct effects against parasitic stages of O. ostertagi. Our results may contribute to the identification of natural anti-parasitic compounds and to interpret the in vivo anthelmintic effects of forage chicory.